Appraisal of fnancial situation of the Polish Banking Sector from 2008 to 2012 = Ocena sytuacji finansowej polskiego sektora bankowego w latach 2008-2012 - Trippner, Paweł (Zielona Góra: Faculty of Economics and Management Press)
The banking system is a very important element of the financial system of a country. As institutions of public trust, banks play a crucial role in the process of transforming savings into investments, which directly affects the country?s economic development. Maintaining the banking sector in a good financial condition guarantees stability of the financial system and economic development of Poland. The article aims to present the essence of operations of banks as financial institutions, present their role in the economy, and describe various methods of appraising their financial condition. In order to fulfil the above goals, a research hypothesis is put forward stating that the financial condition of the banking sector in Poland deteriorated in the analysed period as a result of an adverse impact of turbulence in financial markets and problems in banking sectors in the European Union countries.
Keywords: system bankowy; wskaźnik finansowy; analiza kondycji finansowej; ekonomiczna wartość dodana; pośrednik finansowy; banking system; financial ratio; financial condition analysis; economic value added; financial intermediary